1994
DOI: 10.1095/biolreprod50.4.927
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Molecular Cloning of Bovine Oviduct-Specific Glycoprotein1

Abstract: A specific 85-97-kDa (95-kDa) glycoprotein was found in bovine oviductal tissue and fluid during the follicular phase. In this study, a 95-kDa bovine oviductal glycoprotein (95-kDa BOGP) was purified by wheat germ agglutinin affinity and Mono-Q ion-exchange column chromatography. The first 29 NH2-terminal amino acid residues were determined by gas-phase microsequencing. A cDNA expression library prepared from poly(A)+ RNA isolated from bovine oviducts was screened with a monoclonal antibody to 95-kDa BOGP. A s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(56 citation statements)
references
References 37 publications
2
54
0
Order By: Relevance
“…These characterized clones enclose only one similar unit of 15 amino acids but other related truncated elements are present. The number of potential sites of N-glycosylation ranges from one in the cow (Sendai et al, 1993) to seven in the hamster (Merlen et al, 19941, as deduced from their amino acid sequences (see Table 2). …”
Section: Phylogenetic Conservation Amongmentioning
confidence: 99%
See 1 more Smart Citation
“…These characterized clones enclose only one similar unit of 15 amino acids but other related truncated elements are present. The number of potential sites of N-glycosylation ranges from one in the cow (Sendai et al, 1993) to seven in the hamster (Merlen et al, 19941, as deduced from their amino acid sequences (see Table 2). …”
Section: Phylogenetic Conservation Amongmentioning
confidence: 99%
“…Analyses of post-translational modifications using lectin binding experiments revealed that the mouse (Kapur and Johnson, 1985), bovine (Sendai et al, 1993), and hamster (Malette and Bleau, 1993) oviductins react with the WGA lectin thus indicating the presence of terminal a-D-NeuAc and/or nonterminal p-D-(GlcNAc)2 residues in their oligosaccharide side chains. Bovine oviductin binds peanut lectin (Wegner and Killian, 1992) which is specific for galactosyl (p1,3)Nacetylgalactosamine residues, confirming that it bears Sequence comparison of the repeated motifs found in oviductins.…”
Section: Post-tr Ansl Ational Modificationsmentioning
confidence: 99%
“…Specific proteins such as osteopontin (OPN) (Gabler et al, 2003) and oviduct specific glycoprotein (OGP) (Boice et al, 1990;Sendai et al, 1994;Buhi, 2002) have been identified as secretory products in the bovine oviduct and were found to interact with gametes while also improving the efficiency of IVF (Martus et al, 1998;Killian, 2011). OPN is an extracellular matrix protein (McKee and Nanci, 1996) that, as well as being present in bovine seminal plasma (Cancel et al, 1997), is secreted by the oviduct mucosa.…”
Section: Influence Of the Frtmentioning
confidence: 99%
“…OGPs (Boice et al, 1990;Sendai et al, 1994;Buhi, 2002) are present in the oviduct of every mammal studied to date. They are virtually exclusive to oviduct tissue and their production is greatest during oestrus and ovulation (Buhi, 2002).…”
Section: Influence Of the Frtmentioning
confidence: 99%
“…The restriction enzyme cleavage patterns of the bovine TIMP-1 fragments generated by Pst I and Sma I were analyzed to confirm the identity of the PCR products. In some experiments, the PCR fragments were electrophoresed on 2% agarose gels, capillary blotted onto Hybond N+ positively charged nylon membrane (Amersham, Buckinghamshire, UK), and hybridized with a DIGlabeled PCR probe prepared by the modified PCR method described previously [19].…”
Section: Reverse Transcription-polymerase Chain Reaction (Rt-pcr) Anamentioning
confidence: 99%